The question of ideas in the Muslim world - Bennabi, Malik; El-Mesawi, Mohamed El-Tahir (Islamic Book Trust, 2003)
This book is a translation from French of Malik Bennabi's "Le Probleme des Idees dand le Monde Musulman"